Studies on Germination of the Sandal Seeds. Santalum album Linn. II. Chemical Stimulant for Germination - Nagaveni, H. C.; Srimathi, R. A. (Indian Forester, 1980)
Effect of chemical stimulants such as nitrates and nitrites and plant hormone like gibberellic acid (GA) on tbe dormancy and germination of sandal seeds were studied. Gibberellic acid was found to be effective in bringing down the dormancy period and inducing quick and uniform germination.